Pharmacokinetic Comparisons of Naringenin and Naringenin-Nicotinamide Cocrystal in Rats by LC-MS/MS - Dan Xu; Gui-Qiu Zhang; Ting-Ting Zhang; Bo Jin; Chen Ma (Journal of Analytical Methods in Chemistry)
Naringenin (NAR), 4′,5,7-trihydroxydihydroflavone, has a wide range of pharmacological activities but shows poor water solubility and low bioavailability. The pharmacokinetics and bioavailability of naringenin-nicotinamide cocrystal (NAR-NCT), which offers improved solubility, were evaluated in this study. Rats were orally administered NAR, a physical mixture of naringenin and nicotinamide (NAR + NCT), and NAR-NCT. The relative bioavailability of NAR-NCT was 175.09% of NAR, Cmax was 8.43 and 2.06 times of NAR and NAR + NCT, respectively, Tmax was advanced from 0.49 h to 0.09 h, CL was decreased from 91.1 L/h/kg to 49.1 L/h/kg, and t1/2 was increased from 5.37 h to 8.24 h, highlighting its rapid absorption and slow elimination. This study showed that NAR-NCT could improve the bioavailability of NAR.